FEATURES OF THE IMMUNE RESPONSE TO XENOGENIC TISSUES OF VALVES AND PATCHES OF THE HEART (literature review) - Andrey Vladimirovich Shabaldin; Anna Vladimirovna Blinova; Alexey Valrievih Evtushenko (Медицинская иммунология)
AbstractA global study shows that valvular heart disease still occupies one of the leading places in the structure of mortality from cardiovascular diseases, being one of the leading causes of heart failure, including among the working population. Xenogeneic tissues are widely used in cardiac surgery, both in biological prosthetic heart valves and in vascular and intracardiac patches. Modern methods of chemical treatment of xenogenic tissue aimed at the eliminating of its immunogenicity do not completely remove xenoantigens from the tissue. It is suggested that residual animals’ carbohydrate antigens are a trigger of immune response to xenotissues. At the same time, the role of the immune response to xenogeneic antigens in the induction of inflammation, valve dysfunction, and calcification are discussed.The aim of this review was to summarize scientific research data on the immune response to xenogeneic tissue implanted in the heart and to find ways to overcome this immune conflict.Modification of the pericardium of large animals by various methods does not remove carbohydrate epitopes of the extracellular matrix and cell membranes, which are recognized by pre-existing antibodies of class M and G. The highly dynamic functioning of xenogeneic biological prostheses increases their antigenicity by reducing the primary cross-linking of the extracellular matrix and activating the alternative complement pathway with adsorption on xenogeneic tissue complement component iC3b, as an opsonin for micro- and macrophages. Inflammatory endotypes of individuals are determined by genetically determined increased synthesis of certain cytokines. In particular, rheumatic heart disease, as the basis for the formation of pathology of the native mitral heart valve, is characterized by an increase in TNF-a, INF-g and IL-6. All of these cytokines may be targets for biological therapies aimed at limiting the constitutional inflammatory endotype. OMICS technologies applied to various options for biological xenogeneic heart valve prostheses degradation, taking into account their implantation and a wide clinical examination of patients, can help to find new variants of immune-inflammatory endotypes leading to dysfunction of bioprostheses and identify target molecules through which the antixenogeneic immune response can be inhibited.